1979
DOI: 10.1128/aac.15.4.572
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Agar and Broth Minimum Inhibitory Concentrations of Cefamandole, Cefoxitin, and Cefuroxime

Abstract: The in vitro susceptibility to cefamandole, cefoxitin, and cefuroxime of clinical isolates of Streptococcus faecalis, Klebsiella , and indole-positive Proteus was assayed using minimum inhibitory concentration (MIC) determinations in broth and on solid media. It could be demonstrated that the agar dilution MICs obtained when S. faecalis was tested against cefuroxime and when indole-positive Proteus strains were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…Moreover, norfloxacin was found to be rapidly bactericidal in vivo against the E. coli and K. pneumoniae strains tested. In previous studies, we used the same technique and could demonstrate that the peak concentrations of various cephalosporins and aminoglycosides and metronidazole in TCF were considerably lower in relation to the peak serum levels than was observed for norfloxacin on treatment days 3 and 7 (11)(12)(13)(14). Cefamandole did not noticeably reduce the viable counts of a susceptible strain of Proteus morganii in TCF, although concentrations well above the MIC for that strain were (12).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, norfloxacin was found to be rapidly bactericidal in vivo against the E. coli and K. pneumoniae strains tested. In previous studies, we used the same technique and could demonstrate that the peak concentrations of various cephalosporins and aminoglycosides and metronidazole in TCF were considerably lower in relation to the peak serum levels than was observed for norfloxacin on treatment days 3 and 7 (11)(12)(13)(14). Cefamandole did not noticeably reduce the viable counts of a susceptible strain of Proteus morganii in TCF, although concentrations well above the MIC for that strain were (12).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical importance of such discrepancy also has been emphasized for cefamandole against Enterobacter cloacae (17,24). Rylander et al have demonstrated superior predictability of outcome for certain organisms in experimental infections by broth dilution MIC compared with agar dilution susceptibility testing (23).…”
mentioning
confidence: 99%
“…Although the mechanism(s) responsible for the discrepancies between disk diffusion and broth susceptibility testing was not systematically evaluated, one explanation may be the lower number of organisms tested in agar tests (9,23,25), with less opportunity for expression of resistant variants. Reports indicating superior activity of ticarcillinclavulanate against ticarcillin-resistant P. aeruginosa have been based on disk diffusion (Fosse et al, 14th ICC) or agar dilution susceptibility testing (14; Morisset et al, Proc.…”
mentioning
confidence: 99%
“…Cefamandole is reported to be active against fl-lac' strains when tested by the agar dilution technique, inhibiting such strains at concentrations of 2 ug/ml or less (11), and has been suggested as a possible altemative in the treatment of infections caused by f,-lac+ H. influenzae. Rylander et al observed that for some organisms, the MIC of cefamandole, as determined by the broth dilution technique, is substantially higher than the MIC determined by agar dilution (18). Although Bergeron et al observed no difference between cefamandole MICs for fi-lac' H. influenzae in broth and agar, they noted that cefamandole was much less active against fl-lac' than against f,-lac-strains (4).…”
Section: Resutltsmentioning
confidence: 92%